2020
DOI: 10.3390/agronomy10030387
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Assimilation Area and Chlorophyll Content of Very Early Potato (Solanum tuberosum L.) Cultivars as Influenced by Biostimulants

Abstract: This paper analyses the effects of foliar application of the seaweed extracts Bio-algeen S90 (Ascophyllum nodosum) and Kelpak SL (Ecklonia maxima), as well as the humic and fulvic acids ini HumiPlant (leonardite extract), on the assimilation area and chlorophyll content of very early potato cultivars (‘Denar’, ‘Lord’, Miłek’). The field experiment was carried out in central-eastern Poland over three growing seasons, using Luvisol. The biostimulants were applied according to the manufacturers’ recommendations. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
29
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(34 citation statements)
references
References 37 publications
4
29
1
Order By: Relevance
“…Therefore, in carrot cultivation, healthy, high-quality seeds and roots should be obtained, without any residues of pesticides, heavy metals or mycotoxins harmful to human and animal health. Such effects are provided by ecological cultivations based on biological protection [1,[7][8][9][10][11][12][13][14]. They reduce the number of chemical protection agents, while limiting plant infection by phytopathogens, including toxigenic fungi (Alternaria sp., Fusarium sp.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, in carrot cultivation, healthy, high-quality seeds and roots should be obtained, without any residues of pesticides, heavy metals or mycotoxins harmful to human and animal health. Such effects are provided by ecological cultivations based on biological protection [1,[7][8][9][10][11][12][13][14]. They reduce the number of chemical protection agents, while limiting plant infection by phytopathogens, including toxigenic fungi (Alternaria sp., Fusarium sp.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the principles of good agricultural and horticultural practice, taking into account both environmental protection and high yielding of plants, require modern cultivation methods. Modern cultivation of horticultural plants, including carrots, applies cover crops, living mulches, PGPMs (plant growth-promoting microorganisms) and PGRs (plant growth regulators) protecting the soil against degradation and plants from phytopathogens and stress [14,[41][42][43][44][45][46][47].…”
Section: Introductionmentioning
confidence: 99%
“…Spraying the plants with distilled water resulted in the highest chlorophyll a/b ratio in comparison to control plants. An increase in chlorophyll content in plants where natural preparations were applied during cultivation was noted by many researchers [47][48][49]. Blunden et al [50] observed that the increase in the chlorophyll content in bean, barley, wheat, and maize leaves was caused by the presence of betaine in seaweed extracts.…”
Section: Resultsmentioning
confidence: 97%
“…The effects of these extracts have shown positive results on crop yield and leaf color of lettuce plants [117], on mung bean germination and plant growth [118], and on growth and nutritional quality of spinach [119]. The application of E. maxima extracts on potato plants also had varied effects including the increase of marketable yield [120] the improved tolerance to abiotic stress and total assimilation area [121] whereas contrasting effects on quality were reported with no effects on dry matter, protein, total sugars and vitamin C content [122] or increasing trends on total and true proteins content being observed [123]. The detailed analysis of the extracts identified new plant growth biostimulants, namely eckol and phloroglucinol [119,124,125], while other plant growth regulators such as abscicic acid, gibberellins and brassinosteroids were also detected in commercial products indicating a hormone-like activity [126].…”
Section: Practical Applications Of Biostimulants and Biostimulatory Products On Horticultural Cropsmentioning
confidence: 99%